Assessing Gender Equality in Nepal: A Comparative Study of Progress and Disparities - Parajuli, Chandra; Neupane, Bibek Kanta (NPRC Journal of Multidisciplinary Research, 2025)
This study explores the current state of gender equality in Nepal, emphasizing key aspects such as economic involvement, education levels, health, and political empowerment. Its main goal is to evaluate Nepal’s progress using recent secondary sources, including the Global Gender Gap Index 2025, the Nepal Economic Survey 2023/24, and national reports on gender-based violence and policy enforcement. By examining gender parity scores and comparing Nepal’s position with other South Asian nations, the research seeks to uncover gaps, contradictions in policies and practices, and potential pathways for reform. The research uses a descriptive and comparative approach, analyzing secondary data. Quantitative metrics like global gender rankings, parity scores, labor force participation, civil service representation, and violence statistics are examined to evaluate Nepal’s progress. These figures are compared with similar data from Bangladesh, Bhutan, Sri Lanka, India, Pakistan, and the Maldives to gain regional insights. Additionally, the study reviews policy documents and national survey reports to understand the policy responses and structural challenges women face in Nepal. Findings indicate that Nepal has achieved moderate progress in health and political representation but still significantly trails in economic participation, placing 140th out of 148 countries. Despite implementing gender-responsive policies and specific employment initiatives, women’s involvement in the labor force remains limited, with ongoing structural barriers like social norms, legal shortcomings, and ineffective enforcement. Meanwhile, countries such as Bangladesh and Bhutan demonstrate stronger performance in political empowerment and economic inclusion, providing valuable lessons for Nepal. The study concludes that Nepal’s gender equality policies should extend beyond token representation and budget allocation to focus on comprehensive institutional reforms and social change. To bridge the gender gap and promote inclusive development, it is vital to enhance implementation, enforce accountability, and incorporate regional best practices.